Coronavirus: History, Genome Structure and Pathogenesis - Poonam, B.; Gill, Prabhjot K. (Coronaviruses, 2021)
Background: The positive sense and inordinate large RNA genome enclosed by helical nucleocapsids along with an outermost layer belongs to the family Coronaviridae. The phylogenetic tree of this family has been classified into Class1 as alpha, Class 2 as beta, Class 3 as gamma, and Class 4 as delta CoV. The mammalian respiratory and gastrointestinal tracts are the main target organs of this enveloped virus with misperceived mechanisms. The relevance of this virus family has considerably increased by the recent emergence of the Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS), which are caused by viruses that belong to the beta-CoV group. Aim: Aforesaid illustrations of the emergence of coronavirus diseases over the past two decades, SARS (2002; 2003) and MERS (2012 to present) - the ongoing COVID-19 outbreak has pressurized the WHO to take innovative measures for public health, research and medical communities. The aim of the present review is to have proficiency in the coronavirus replication and transcription process which is still in its infancy. Conclusion: As an outcome of epidemics, it is being recognized as one of the most advancing viruses by the virtue of high genomic nucleotide substitution rates and recombination. The hallmark of coronavirus replication is discontinuous transcription resulting in the production of multiple subgenomic mRNAs having sequences complementary to both ends of the genome. Therefore, the complete genome sequence of coronavirus will be used as a frame of reference for comprehending this classical phenomenon of the RNA replication process. Finally, research on the pathogenesis of coronaviruses and the host immunopathological response will aid in designing vaccines and minimizing the mortality rate.
Keywords: SARS